Lens epithelial cell growth on the anterior optic of 2 hydrophobic intraocular lens models. Issue 2 (February 2016) - Weinberg, Tamir; Klein, Ido; Zadok, David; Huszar, Monica; Harari, Ayelet; Ezov, Nathan; Kleinmann, Guy
Abstract : Purpose : To evaluate lens epithelial cell (LEC) proliferation on the anterior optic of 2 types of hydrophobic intraocular lenses (IOLs). Setting : Harlan Biotech Israel and Kaplan Medical Center, Rehovot, Israel. Design : Experimental study. Methods : Ten New Zealand white rabbits had crystalline lens removal and implantation of an Acrysof IOL in 1 eye (Group 1) and a Tecnis IOL in the fellow eye (Group 2). A weekly biomicroscopy examination was performed during the 2‐week study duration, after which the rabbits were humanely killed. The eyes were enucleated, and the complexes containing the IOL and the capsular bag were evaluated for the presence of LECs and large cells (macrophages and giant cells) on the IOL anterior optic and for proteinaceous matrix deposits along the capsulorhexis margin. Results : Lens epithelial cell were detected on all of the IOLs in Group 1 and on none in Group 2 ( P < .001). Areas of proteinaceous matrix deposits adjacent to the edge of the capsulorhexis were detected on 8 IOLs in Group 1 and on none in Group 2 ( P < .001). Large cells were identified on all IOLs in Group 1 and on 9 IOLs in Group 2 ( P = 1.0). No difference in the general inflammation markers was found between the 2 IOL types ( P = .234). Conclusions : Lens epithelial cell with corresponding proteinaceous matrix deposits were significantly more abundant on the IOLs in Group 1 than on the IOLs in Group 2. There was no difference in the presence of large cells or in general inflammation markers between the 2 IOL types. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.